The anterior-posterior axis emerges respecting the morphology of the mouse embryo that changes and aligns with the uterus before gastrulation - Mesnard, D (2018)
Background: When the anterior-posterior axis of the mouse embryo becomes explicit at gastrulation, it is almost perpendicular to the long uterine axis. This led to the belief that the uterus could play a key role in positioning this future body axis. Results: Here, we demonstrate that when the anterior-posterior axis first emerges it does not respect the axes of the uterus but, rather, the morphology of the embryo. Unexpectedly, the emerging anterior-posterior axis is initially aligned not with the long, but the short axis of the embryo. Then whether the embryo develops in vitro or in utero, the anterior-posterior axis becomes aligned with the long axis of embryo just prior to gastrulation. Of three mechanisms that could account for this apparent shift in anterior-posterior axis orientation-cell migration, spatial change of gene expression, or change in embryo shape-lineage tracing studies favor a shape change accompanied by restriction of the expression domain of anterior markers. This property of the embryo must be modulated by interactions with the uterus as ultimately the anterior-posterior and long axes of the embryo align with the left-right uterine axis. Conclusions: The emerging anterior-posterior axis relates to embryo morphology rather than that of the uterus. The apparent shift in its orientation to align with the long embryonic axis and with the uterus is associated with a change in embryo shape and a refinement of anterior gene expression pattern. This suggests an interdependence between anterior-posterior gene expression, the shape of the embryo, and the uterus.